Malaysia SMEs Award Winners’ Environmental Scanning Practice - Hamedon, Siti Rohimi (2012)
This study examines the effects of owner manager characteristics on environmental scanning practice of Malaysia‟s SMEs Award Winners, E50 SMEs. It investigates the relationship between E50 SMEs owner manager environmental scanning need and environmental scanning practice. Based on the constructs of the measures, a research scale was developed for the study and data were collected via self-administered mail survey among the E50 SMEs in Malaysia. The results revealed that owner manager environmental scanning need (the perceived importance to stay abreast of the business environment) and owner manager environmental scanning interest (the role of environmental scanning to the organization) is the predictor of environmental scanning practice. Implications of the findings in theory and practice for SMEs owner managers and practitioners are also discussed. The study's limitations and future research directions are consequently addressed